Tacitus' annals - Mellor, Ronald (Oxford University Press, 2010)
Tacitus' Annals is the central historical source for first-century C.E. Rome. It is prized by historians since it provides the best narrative material for the reigns of Tiberius, Claudius, and Nero, as well as a probing analysis of the imperial system of government. But the Annals should be seen as far more than an historical source, a mere mine for the reconstruction of the facts of Roman history. While the Annals is a superb work of history, it has also become a central text in the western literary, political, and even philosophical traditions - from the Renaissance to the French and America.
Keywords: Tacitus, Cornelius. -- Annales.; Tacitus, Cornelius -- Criticism and interpretation.; Tacitus, Cornelius; Annales (Tacitus, Cornelius); Rome -- Historiography.; HISTORY -- Ancient.; Historiography; Rome (Empire); Criticism, interpretation, etc.